Efektivitas Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama Kota Kediri - Mohammad Muizzudin; Achmad Asfi Burhanudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Mediation is the process of resolving disputes through a negotiation or consensus process by the parties assisted by a mediator who has no authority to interrupt or impose a settlement. In reality, the implementation of mediation is still less effective in resolving a case, evidenced by the least of things successfully resolved by mediation. The problem that will be discussed in this research is about the effectiveness of mediation as a means of reconciling the cause, whose main goal is to reduce the number of cases, and also to know the success rate of mediation. Especially in the case of divorce in Kediri city religious court. The method used in this research is a case study, which is a research conducted intensively, detailed and in-depth to a particular organization, institution or symptom, and seeks to maintain the integrity of the object. The object of this study was mediation in the Kediri religious court about mediation on divorce in 2017. Field research as complementary. This study uses qualitative analysis by thinking inductive-analytic descriptionist-analytical as well as using the normative-juridical approach. And in collecting data using observations, interviews and document searches. Based on the results of the research, it is known that mediation in the case of divorce that occurred in Kediri religious court year 2017 ineffective. The most prominent cause of this is the strong determination of litigants to divorce